Zaviralci ureaze - Frlan, Rok (Farmacevtski vestnik, 2013)
Urease is an enzyme that catalyzes the hydrolysis of urea to ammonia and carbamate. Ureolytic activity of human pathogens, such as Helicobacter pylori,Proteus spp. and others is thought to be a causative factor of many clinical conditions, such as peptic ulcer and urinary infection stones. The most efficient therapy which is quite successful at the moment is complete eradication of bacteria and treatment of disease symptoms. Because of the increasing resistance to antibacterial agents the design of new treatment routes is becoming a new focal point to control these diseases in the future. One of perspective targets in the design of novel inhibitors and vaccines is urease. Many inhibitors have been developed so far, however only one compound,acetohydroxamic acid, has been used clinically for the treatment of urinary tract infections.
Keywords: Helicobacter pylori; peptična razjeda; sečni kamni; ureaze; zaviralci